Formulation of Local Food Ingredients from Red Beans and Catfish in the Form of Nugget Snacks as Wasted Under Five Years Old Children Supplementary Food: : Analysis of Nutritional and Organoleptic Quality - Budi, Dhiah Widyaningtyas; Palupi, Fitria Dhenok; Setyobudi, Sugeng Iwan (Journal of Local Therapy, 2025)
This study aims to analyze the empirical nutritional quality (energy, protein, fat, carbohydrates, vitamin A, calcium, iron and phosphorus), organoleptic quality and determine the best treatment level of Nuggets with red bean and catfish formulation as supplementary food for wasted under five years old children. This study employed an experimental approach with a Completely Randomized Design (CRD) consisting of three treatment levels. The nugget formulation was developed by modifying the proportions of catfish, chicken meat, and red beans with the following ratios: P0 = 0:100:0, P1 = 25:48:27, P2 = 33:40:27, and P3 = 41:32:27. Organoleptic tests by 25 semi-trained panelists assessed color, aroma, taste, and texture using a hedonic scale. Statistical analysis utilized Kruskal-Wallis and Mann-Whitney tests to determine significant differences, while the best formulation was identified using effectiveness index analysis. In this study the best formulation, consisting of 41% catfish, 32% chicken, and 27% red beans (P3), showed an Overcome Value (OV) of 0.884 and provided 359.94 kcal, 15.67g protein, 20.94g fat, and 27.17g carbohydrates per 100g. No significant preference difference was found between the control and P3 treatments. Future studies should focus on optimizing frying conditions to improve nugget color.